Microscopic Evaluation of the Effect of Oral Microbiota on the Development of Bisphosphonate-Related Osteonecrosis of the Jaws in Rats - Felipe M. Silveira; Adriana Etges; Marcos B. Correa; Ana Carolina U. Vasconcelos (eJournal of Oral Maxillofacial Research)
Objectives: Osteonecrosis of the jaws is a side effect associated with the use of bisphosphonates. Using histologic analysis, this study aimed to evaluate the influence of microbial colonies in the development of osteonecrosis in the jaws of rats subjected to nitrogenous and non-nitrogenous bisphosphonates, undergoing surgical procedures.